Integration of augmented reality smart glasses as assembly support: a framework implementation in a quick evaluation tool. (20th June 2023) - Danielsson, Oscar; Syberfeldt, Anna; Holm, Magnus; Thorvald, Peter
Augmented reality smart glasses (ARSG) have been successfully used as operator support in production. However, their use is not yet widespread, likely in part due to a lack of knowledge about how to integrate ARSG into production. This lack of knowledge can also make it hard to estimate whether this is a worthwhile investment. Our solution is to provide an online evaluation tool to help production planners estimate the likelihood that ARSG will be worth the investment cost in specific production cases. Based on a strawman design, multiple design iterations were followed by a pilot test performed by participants from different manufacturing companies involved in planning production for operators. A Likert scale survey was used to evaluate the tool. The results show a slightly positive evaluation of the tool with suggestions for improvement, including widening the scope and granularity of the tool. Future works include further iterations and case studies. [Submitted 9 April 2021; Accepted 31 July 2021]